Concurrence of lower jaw skeletal anomalies in triploid Atlantic salmon (Salmo salar L.) and the effect on growth in freshwater - Gianluca Amoroso; Cobcroft, JM; Mark Adams; Ventura, T; Christopher Carter (2016)
Triploid Atlantic salmon populations are associated with higher prevalence of lower jaw skeletal anomalies affecting fish performance, welfare and value deleteriously. Anomalous lower jaw can be curved downward (LJD), shortened (SJ) or misaligned (MA). Two separate groups of triploid Atlantic salmon (~12 g) with either normal lower jaw (NOR) or SJ were visually assessed four times over three months for presence and concurrence of jaw anomalies (with severity classified) and opercular shortening to understand the relatedness of these anomalous developmental processes. The prevalence of jaw anomalies increased in both groups over time (NOR group – SJ, LJD and MA combined 0–24.5%; SJ group – LJD and MA combined 17–31%). SJ and LJD occurred both independently and concurrently whereas MA exclusively concurred with them. All three anomalies could be concurrent. Severity of both LJD and SJ increased in the SJ group only. Opercular shortening recovery was observed in both groups but at a slower rate in the SJ group. The SJ group specific growth rate (SGR) was significantly ( P < 0.05) lower than the NOR group. This study demonstrated the concurrence of SJ, LJD and MA and showed possible deleterious consequences deriving from the conditions.